Antimicrobial effects of leaves of Indian herbal plants with reference to peptic ulcer - Mayank Kulshreshtha; Harinath Dwivedi; Manjul Pratap Singh (Wolters Kluwer Medknow Publications, 2018)
Objective: Gastrointestinal (GI) diseases affect a large part of the population. Peptic ulcer (PU) which is very common disease affects the stomach and duodenum. Many microbial species such as Staphylococcus aureus, Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, Aspergillus tubingensis etc are responsible for PU directly or indirectly. Materials and Methods: The aim of this study was to find out the effects of aqueous and ethanolic extracts of leaves of Quisqualis indica, Elaeocarpus ganitrus and Prosopis cineraria on PU-associated microorganism. Minimum inhibitory concentration (MIC) and the synergistic effects of selected plant extracts with renowned standards (ciprofloxacin, norfloxacin, ketoconazole, and fluconazole) were estimated. Disc diffusion and solid dilution methods were used for the determination of antimicrobial effects and MIC. Results: Studies revealed that the plant extracts were highly effective against selected microbes. Escherichia coli was found to be the least affected microbial species. Different infectious diseases of GI tract might be cured using formulations having these selected plant extracts. The zone of inhibitions (ZOI) was observed ranging from 2.3 ± 0.57 to 12.3 ± 0.59 mm. The maximum ZOI was observed (12.3 ± 0.59 mm) for ethanolic extract of Elaeocarpus ganitrus against Pseudomonas aeruginosa. Conclusion: The herbal extracts were found to be highly promising against selected microbial species associated with PU.